Cutaneous adverse events due to checkpoint inhibitors – a retrospective analysis at a tertiary referral hospital in Switzerland 2019-2022 - Furrer-Matcau, Clara; Sieber, Chloé; Lehnick, Dirk; Brand, Christoph Urs; Hug, Balthasar (Frontiers in Oncology, 2024)
IntroductionCheckpoint inhibitors are increasingly important in anti-cancer treatment. Therefore, knowledge of immune-related cutaneous adverse events (ir-cAE) is crucial for therapy management and continuation.ObjectiveThe study aimed to analyze the incidence of cutaneous adverse events caused by checkpoint inhibitor therapy, including their clinical presentation, management, and impact on further treatment.MethodsThis is a descriptive, monocentric retrospective study that uses data from the electronic health record system at a tertiary referral hospital in Central Switzerland from September 2019 to September 2022. The electronic health records of patients who received a therapy with checkpoint inhibitors were examined for age, sex, type of immunotherapy, time to occurrence of ir-cAEs, characteristics of the ir-cAEs, the treatment approach, and the continuation or cessation of the therapy due to ir-cAEs.ResultsOut of 431 patients, for 131 patients (30.4%) at least one ir-cAE event was documented. In particular, 109 (25.3%) experienced pruritus and 61 (14.2%) showed a maculopapular exanthema. The severity of the ir-cAE was mild in 88 patients (67.2% out of those with ir-cAEs). Ir-cAE were observed in 10 out of 20 patients (50%) treated with ipilimumab/nivolumab and in 15 out of 24 (62.5%) treated with durvalumab. In 15 patients (3.5%), checkpoint inhibitor therapy had to be discontinued due to cutaneous side effects.ConclusionsThis study showed that approximately one third of the patients experienced ir-cAEs. The most frequently observed ir-cAEs were pruritus, maculopapular exanthema and xerosis cutis. In general, the dermatological manifestations are mild and responsive to topical treatment or self-limiting with no requirement for treatment interruption.